Citation analysis of the University of the Philippines College of Dentistry Library theses with implications on collection development - Castro, Maria Nimfa V. (2013)
The vast flow of information has been a challenge to librarians nowadays due to technological advancements. The provision of relevant materials to meet the needs of library users is one of the responsibilities of librarians. To be able to know the relevance of a library's collection is to evaluate it.